Medical Malpractice in the Juridical Review of the Indonesian Legal System: Malpraktek Medis dalam Tinjauan Yuridis Sistem Hukum Indonesia - Isnaini Pratami, Lulu (UPMI Proceeding Series, 2023)
Based on the results of the research and discussion, it was concluded that until now Indonesia does not yet have a specific law on medical malpractice. From the Indonesian legal system, not all regulate medical malpractice. What regulates it, namely Civil Law, Criminal Law and Administrative Law. The laws concerned, among others: Law No. 29 of 2004, Law no. 36 of 2009, Law no. 44 of 2009 which of these provisions can provide a basis for patients to file legal remedies. Regulations that are not included in the hierarchy of the Indonesian legal system but are related to medical malpractice include: Minister of Health Regulation No 269/Menkes/Per/III/2008 concerning Medical Records, Minister of Health Regulation No 512/Menkes/Per/IV/2007 concerning Practice Permits and Implementation of Medical Practice, Regulation of the Minister of Health No: 585/Men.Kes/Per/IX/1989 Concerning Approval of Medical Actions. Juridically, cases of medical malpractice in Indonesia can be resolved by relying on several legal bases, namely: the Criminal Code, the Civil Code, Law no. 8 of 1999, Law no. 29 of 2004, Law No. 36 of 2009, Law No. 44 of 2009, Regulation of the Minister of Health No. 585/Menkes/Per/IX/1989, Minister of Health Regulation No 512/Menkes/Per/IV/2007, Minister of Health Regulation No 269/Menkes/Per/III/2008.